Modernidade em desalinho: costumes, cotidiano e linguagens na obra humorística de Raul Pederneiras (1898-1936) - Silva, Rogério Souza (2014)
This thesis performs a discussion of the humorous production of Raul Pederneiras. The starting point of the research is the year 1898, when the artist published his first caricature, in O Mercurio. Aspects of modern urban area of Rio de Janeiro were among his favorite subjects. He noted the wide gap between a modernity seen as ideal, which was modeled on the North Atlantic world, and its application to the Brazilian reality. But his vision was global and international issues were among their concerns. Besides caricaturist, Raul Pederneiras wrote texts of humor with high quality, getting to play with words and making numerous puns. He was a multifaceted character, which made it more interesting. Among its activities, may be included journalist, playwright, poet, painter, composer, propagandist, police officer and professor of international law, having written several books in his career. The final milestone of the research is the year 1936, when Raul published his latest book, titled Musa travessa: ruma de rimas sem rumo, having already clear signs of decline in his artistic and intellectual production. In this historical moment, there is a look of the comedian to the change process by which the country was in that context